Development administration in a changing society / edited by R.D.Sharma - Sharma, R.D.(ed.) (New Delhi, 1987)
Development Administration in a Changing Society" The book is an outcome of the efforts of the Post-Graduate Centre of Public Administration, Simla-1 which had organised a seminar in November, 1984. he book focuses attention on development as a concept and economic conditions and pro blems of an under developed state.
Keywords: Public Administration